2018
DOI: 10.1002/app.46888
|View full text |Cite
|
Sign up to set email alerts
|

Thermal behaviors and flame retardancy of novel flame‐retardant, oil‐filled styrene–ethylene–butadiene–styrene block copolymer–polypropylene materials

Abstract: A novel halogen‐free flame‐retardant material consisting of a novel cyclotriphosphazene‐based char‐forming agent, aluminum diethyl phosphinate, nickel trioxide (Ni2O3), an oil‐filled styrene–ethylene–butadiene–styrene block copolymer, and polypropylene was studied. On the basis of their UL‐94 ratings and limiting oxygen index (LOI) data, the flame retardants exhibited very effective flame‐retardant properties in the material. When the loading of flame retardant (FR) was only 35 wt %, the flame‐retardant materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…In recent years, traditional halogen‐based flame retardants have high‐efficiency flame retardance have been used in UPR market. However, the halogen‐containing materials will release large amounts of corrosive gas and toxic smoke gases when they are burning, which endangers human health and property safety . Hence, the current research studies are more focused on halogen‐free, low‐smoke, low‐toxic, and environmentally friendly flame retardants, such as magnesium hydroxide (MH), expandable graphite (EG), intumescent flame retardants, and phosphorus containing flame retardants.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, traditional halogen‐based flame retardants have high‐efficiency flame retardance have been used in UPR market. However, the halogen‐containing materials will release large amounts of corrosive gas and toxic smoke gases when they are burning, which endangers human health and property safety . Hence, the current research studies are more focused on halogen‐free, low‐smoke, low‐toxic, and environmentally friendly flame retardants, such as magnesium hydroxide (MH), expandable graphite (EG), intumescent flame retardants, and phosphorus containing flame retardants.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the expanded carbon layer could reduce further degradation as a physical barrier. 50 Through thermal analysis, the addition could play an important role as a highly efficient flame retardant system.…”
Section: Thermal Decompositionmentioning
confidence: 99%
“…To evaluate the flammability of PP materials, 50,51 LOI and UL-94 were implemented as listed in Table 1. It could be seen that the LOI values kept increasing with the addition of the fire retardant.…”
Section: Flame Retardant Propertymentioning
confidence: 99%
“…So far, many researchers have worked widely on polymeric nanocomposites with the addition of nanosized inorganic fillers. In this area, the main focus of the researchers was on nanocomposites reinforcement, barrier properties, electro-optical properties, biological properties, and flame-retardant properties. Previous researchers, like Gilman, Wilkie and Jang, Alexandridis et al, Camino et al, Camino et al, and Hu et al, have applied polymeric-based nanocomposites for advancement of flame-retardant properties by combining small amounts of nanoadditives, such as montmorillonite (MMT), carbon nanotubes (CNT), graphene, layered double hydroxides (LDHs), and polyhedral oligomeric silsesquioxane (POSS) into the polymer matrix. Many research articles reported a 2D nanomaterial-reinforced polymer composite showing flame-retardant properties such as Hbn/PTFE composites, multifunctional MoS 2 hybrid materials, carbon fiber/acrylonitrile-butadienestyrene composites, conductive boron nitride/polyimide composites, thermal conductivities for PPS dielectric nanocomposites, and multifunctional boron nitride nanosheets .…”
Section: Introductionmentioning
confidence: 99%
“…In this area, the main focus of the researchers was on nanocomposites reinforcement, barrier properties, electro-optical properties, biological properties, and flame-retardant properties. 19−24 Previous researchers, like Gilman, 19 Wilkie and Jang, 25 Alexandridis et al, 26 Camino et al, 27 Camino et al, 28 and Hu et al, 29 31 carbon fiber/acrylonitrile-butadienestyrene composites, 32 conductive boron nitride/polyimide composites, 33 thermal conductivities for PPS dielectric nanocomposites, 34 and multifunctional boron nitride nanosheets. 35 Graphene is coming up as a very interesting support material for flame retardation systems.…”
Section: ■ Introductionmentioning
confidence: 99%